Oil price volatility and airlines’ stock returns: evidence from the global aviation industry - Horobet, Alexandra; Zlatea, Marinela Luminita Emanuela; Belascu, Lucian; Dumitrescu, Dan Gabriel (Journal of Business Economics and Management, 2022)
The paper explores the long versus short-term attributes of the airline industry exposure to oil price risk in a macroeconomic framework that emphasizes the interconnections between various risk factors, which is the main contribution to the research in the field. A panel ARDL model and PMG estimator have been applied on monthly data between 2007 and 2020 to investigate the long-term equilibrium relationship between airline companies’ stock prices, oil price risk, financial market volatility, currency risk, inflation, and maturity risk. The negative impact of oil price risk on airlines’ stock prices is significant, robust, and pervasive, and is coupled with a concerning exposure to the US dollar currency risk. As another contribution, the paper analyses the prospects and challenges of the airline industry in dealing with oil price risk in the post-pandemic world. The results point towards the need of the airline industry to rethink its strategic decisions in the more uncertain and unpredictable post-pandemic world, requiring a more comprehensive approach of the complex and dynamic network of risk exposures and a reconsideration of hedging policies.